A Literacy and Numeracy Model to Enhance the Independent Learning Education for Islamic Elementary School Teachers - Ahwy Oktradiksa; Mujahidun Mujahidun; Carolyn Hunt (Al Ibtida: Jurnal Pendidikan Guru MI, 2023)
AbstractThis study aims to determine the effectiveness of the literacy-numeration model in increasing educational learning independence for class teachers and students at Madrasah Ibtidaiyah, Magelang Regency, Indonesia. Qualitative and quantitative approaches were used as research methods. Data were collected by using interviews, observation, and documentation techniques. The collected data were then analysed with hypothesis test, validity, reliability, normality, paired t-test, and simple independent-test. This research was conducted on a subject population of 43 Madrasah Ibtidaiyah class teachers. The results showed the effectiveness of the development of independent learning education with literacy and numeracy models for class teachers and students of Madrasah Ibtidaiyah in Magelang Regency, Indonesia. The results of the output test "paired Samples Test" yielded that Sig.(2-tailed) was 0.000 <0.05, thus, Ho was rejected and Ha was accepted. This result suggest that there is a significant effect of the literacy-numeration model on the development of independent learning education for students and teachers of Madrasah Ibtidaiyah in Magelang Regency, Indonesia.Keywords: literacy-numeration model, independent learning education, Islamic elementary school teachers. Â AbstrakPenelitian ini bertujuan untuk mengetahui efektivitas model literasi-numerasi untuk meningkatkan kemandirian belajar pendidikan bagi guru kelas dan siswa di Madrasah Ibtidaiyah Kabupaten Magelang, Indonesia. Pendekatan kualitatif dan kuantitatif digunakan sebagai metode penelitian. Teknik pengumpulan data menggunakan wawancara, observasi, dokumentasi. Analisis data menggunakan uji hipotesis, validitas, reliabilitas, normalitas, uji-t berpasangan, dan uji-independent sederhana. Penelitian ini dilakukan pada subjek populasi sebanyak 43 orang guru kelas Madrasah Ibtidaiyah. Hasil penelitian menunjukkan keefektifan pengembangan pendidikan merdeka belajar dengan model literasi dan numerasi untuk guru kelas Madrasah Ibtidaiyah di Kabupaten Magelang, Indonesia. Berdasarkan hasil output â€œpaired Samples Testâ€ diketahui Sig.(2-tailed) adalah 0,000 < 0,05 maka Ho ditolak dan Ha diterima. Maka dapat dapat disimpulkan bahwa terdapat pengaruh yang signifikan keefektifan model literasi-numerasi terhadap pengembangan pendidikan merdeka belajar bagi guru kelas Madrasah Ibtidaiyah di Kabupaten Magelang.Kata kunci: model literasi-numerasi, pendidikan merdeka belajar, guru madrasah ibtidaiyah.